Uso do método do trabalho essencial de fratura (EWF) para avaliar a tenacidade de blendas poliméricas - Yamakawa, Roberto Seiji (Universidade Federal de São Carlos, 2005)
Initially it was made a well elaborated study on the essential work of fracture method (EWF) using the polyamide 6 (PA6) because this polymer shows high difficult to evaluate its toughness. The PA6 is a semi-crystalline polymer, so its mechanical properties are highly affects by the specimen processing conditions. This material is also highly susceptible to the notch, so it is necessary to study how the conditions to obtain the notch and pre-crack can affect the applicability of the EWF method. The best specimen dimension to work in plane stress condition was determined for the uniaxial tensile test. This first study allowed determining the best specimen condition to apply the EWF method. The EWF method was used to evaluate the toughness of polymeric blends. One of the blend was prepared with a semi-crystalline matrix (PA6/ABS) and other with amorphous matrix (PC/ABS). It was also studied the efficiency of the MMA-MA compatibilizer on the PA6/ABS blend toughness. The results allowed concluding that the EWF method was able to verify the improvement of toughness in the blends when compared with the pure polymers as well as the improvement of toughness when the compatibilizer is added to the blend. It was also studied the influence of specimen thickness, strain rate and injection molding conditions like injection speed and mold temperature on the parameters of EWF method. The results allowed concluding that all variables affected the specific essential work of fracture, we, while the specific nonessential work of fracture, βwp, was not affect by that variables, except in the highest test speed for PA6 and in the different thickness for the PA6 and PA6/ABS/MMA-MA blend.
The use of essential work of fracture (EWF)method to evaluate the toughness of polymeric blends
Keywords: Mecânica da fratura; EWF; Tenacificação; Poliamidas (nylon 6); Policarbonatos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA